Training the Leadership Style of Swimming Coaches in Improving Athlete Achievement - Rahayu Prasetiyo; Novita Nur Synthiawati; Arsika Yunarta; Zoki, Achmed (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
This devotion aims to improve the coach's ability to choose a leadership style to apply during the training process during his time as a coach. The method used is mentoring, the result of dedication to improve the coach's ability to choose a leadership style given by researchers by providing training on coach leadership styles to improve athlete achievement which aims to find out participants' responses about the importance of swimming coach leadership styles in improving athlete achievement. Therefore, from the results of this service, 87 % of participants' responses to training through the leadership style of swimming coaches in improving athletes' achievements are categorized as Good.